2022
DOI: 10.3390/cancers14215276
|View full text |Cite
|
Sign up to set email alerts
|

Timely Leukapheresis May Interfere with the “Fitness” of Lymphocytes Collected for CAR-T Treatment in High Risk DLBCL Patients

Abstract: The development of chimeric antigen receptor (CAR)-T cell therapy has revolutionized the treatment of hematological diseases. However, approximately 60% of patients relapse after CAR-T cell therapy, and no clear cause for this failure has been identified. The objective of the Bio-CAR-T BS study (ClinicalTrials.gov: NCT05366569) is to improve our understanding of the lymphocyte harvest to maximize the quality of the CAR-T cell product. Of the 14 patients enrolled, 11 were diagnosed with DLBCL, 2 with PMBCL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While several groups have tried to evaluate T‐cell fitness by thorough analyses of T‐cell subsets, that is, naïve/stem cell memory, central memory, effector memory and effector T cells, or by quantifying cytokine production, 11–15 it has been difficult to evaluate T‐cell fitness in clinical practice. Because the CD4/CD8 ratio among T cells in peripheral blood declines with ablative chemotherapies, it is a convenient surrogate marker of T‐cell fitness 16–18 . In addition, as it has been reported that proliferation and therapeutic effects of CAR‐T cells are improved by a manufacturing process in which collected T cells were separated into CD4 + cells and CD8 + cells, and CAR was introduced with a balanced CD4/CD8 ratio, 19,20 our results suggest that the CD4/CD8 ratio of T cells may also affect efficiency of the subsequent manufacturing process.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While several groups have tried to evaluate T‐cell fitness by thorough analyses of T‐cell subsets, that is, naïve/stem cell memory, central memory, effector memory and effector T cells, or by quantifying cytokine production, 11–15 it has been difficult to evaluate T‐cell fitness in clinical practice. Because the CD4/CD8 ratio among T cells in peripheral blood declines with ablative chemotherapies, it is a convenient surrogate marker of T‐cell fitness 16–18 . In addition, as it has been reported that proliferation and therapeutic effects of CAR‐T cells are improved by a manufacturing process in which collected T cells were separated into CD4 + cells and CD8 + cells, and CAR was introduced with a balanced CD4/CD8 ratio, 19,20 our results suggest that the CD4/CD8 ratio of T cells may also affect efficiency of the subsequent manufacturing process.…”
Section: Discussionmentioning
confidence: 70%
“…Because the CD4/ CD8 ratio among T cells in peripheral blood declines with ablative chemotherapies, it is a convenient surrogate marker of T-cell fitness. [16][17][18] In addition, as it has been reported that proliferation and therapeutic effects of CAR-T cells are improved by a manufacturing process in which collected T cells were separated into CD4 + cells and CD8 + cells, and CAR was introduced with a balanced CD4/CD8 ratio, 19,20 our results suggest that the CD4/CD8 ratio of T cells may also affect efficiency of the subsequent manufacturing process. The adverse effect of an unfavourable CD4/CD8 ratio on CAR-T cell manufacturing may be minimized by optimizing the manufacturing process.…”
Section: Discussionmentioning
confidence: 74%
“…In the Bio‐CAR‐T BS study, patients who received early pre‐emptive lymphocyte apheresis had a significantly different T cell population compared to those who underwent standard lymphocyte apheresis. Specifically, early T cell collection resulted in a higher CD4+/CD8+ ratio, higher CD4+ naive T cells, lower CD4+ effector memory T cells, and lower CD8+ terminally differentiated cell when compared to T cells collected in the standard group 43 …”
Section: Challenges and Proposed Solutions To Superior Car‐t Design A...mentioning
confidence: 91%
“…Specifically, early T cell collection resulted in a higher CD4+/CD8+ ratio, higher CD4+ naive T cells, lower CD4+ effector memory T cells, and lower CD8+ terminally differentiated cell when compared to T cells collected in the standard group. 43 Finally, a considerable challenge is that we do not have long-term follow-up data to know which clinical setting (i.e. line of therapy) is optimal for delivering CAR-T cells.…”
Section: Ch a L L E Nge S A N D Propose D Solu Tions To Su Per Ior Ca...mentioning
confidence: 99%
“…[7,8] Accumulating evidence has shown that pre-infusion CAR T cell phenotypes, including exhaustion status and proportions of T cell differentiation subsets, can influence the durability of response. [9][10][11][12] The majority of current CAR T cell manufacturing processes do not consistently make products with high levels of lessdifferentiated T cells, such as central memory (T CM ) and stem cell-like memory (T SCM ), that are associated with durable responses in patients. [13][14][15][16][17] In fact, a recent phase I clinical trial enriching for naïve and memory phenotypes (CD62L+) before viral transduction allowed for lower doses of CAR T cell infusion and resulted in seven out of ten patients achieving complete response (CR) with durability at 18 months.…”
Section: Introductionmentioning
confidence: 99%